Statistical handbook of Japan 2005 (The Japan Statistical Association, 2005)
This handbook is designed to provide a clear and coherent overview of present-day Japan through statistics. It provides statistical tables, charts, and photographs to portray conditions in modern-day Japan from a variety of perspectives, including dempgraphics, economic and social trends, and culture.